Immune reconstitution inflammatory syndrome in splenic Pneumocystis jirovecii infection: A case report. (2023) - Kojima, Hiroki; Tanaka, Masaru; Imamura, Akifumi
Abstract: To the best of our knowledge, the present report is the first to describe immune reconstitution inflammatory syndrome (IRIS) in a case of Pneumocystis jirovecii ( P. jirovecii ) infection of the spleen. A 45-year-old, men who have sex with men patient presented with constipation, abdominal pain, nausea, fever, and weight loss. Human immunodeficiency virus infection and P. jirovecii pneumonia were diagnosed. Abdominal computed tomography revealed multiple, hypodense, cystic lesions in the spleen. Based on the histopathological findings of the lesion obtained from a percutaneous splenic biopsy, extrapulmonary P. jirovecii infection of the spleen was diagnosed. Trimethoprim/sulfamethoxazole was administered for 21 days, and antiretroviral therapy was initiated ten days after the former regimen was begun. Temporary enlargement of the splenic lesions and fever recurrence were observed after the trimethoprim/sulfamethoxazole regimen was completed. However, the clinical course was favorable, with no splenic rupture or splenic bleeding. Our investigation suggested that additional therapy, such as corticosteroid administration, may not be required for IRIS in a splenic P. jirovecii infection, but further research is needed for a definitive conclusion. Highlights: We report a case of immune reconstitution inflammatory syndrome (IRIS) in a Pneumocystis jirovecii infection of the spleen. The outcome was favorable without additional treatment for immune reconstitution inflammatory syndrome. Careful observation may be an option for managing IRIS in an extrapulmonary Pneumocystis jirovecii infection.